COMPOSITION OF SOCIAL INSURANCE COSTS AND GUIDELINES FOR EFFECTIVE USE - Beknazarov Zafarjon Ergashevich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article explores the financial analysis of Uzbekistan's social insurance system, encompassing economic-statistical analyses of different social insurance types and the results of pension and allowance disbursement software. It discusses the rise in recipients of social benefits and material assistance for low-income families, along with their financial sources. The implementation of the social insurance system necessitates financial resources, making social funds integral to economic mechanisms for income redistribution. These funds, whether state or non-state, depend on factors like the national economic development model. Acknowledging their role in financial relations, social funds have a specific financial purpose, crucial in priority areas. Ongoing research focuses on effective organization and financing of the social protection system, emphasizing the development of voluntary and mandatory medical insurance, improving unemployment benefit procedures, and enhancing pension system stability. Recent initiatives in Uzbekistan include the revision of pension procedures, fundamental pension system reform, laws on compulsory health insurance, and the development of the